Three versus seven days of apramycin treatment for post-weaning diarrhoea in piglets: clinical and resistance gene outcomes from a cluster-randomised field trial - Emma Smedsgaard Byskov; Laura Goncalves Pereira; Mattia Pirolo; Ken Steen Pedersen; John Elmerdahl Olsen; Luca Guardabassi; Peter Damborg (Porcine Health Management, 2026)
Abstract Background Post-weaning diarrhoea (PWD) is a major driver of antimicrobial use in pigs. Optimising treatment duration may reduce selection pressure while maintaining clinical efficacy, but under EU Regulation (EU) 2019/6 veterinarians must adhere to authorised treatment durations, creating a need for evidence to support label changes. This study aimed to determine whether a 3-day apramycin treatment is non-inferior to the standard 7-day course for clinical cure of PWD and to assess its effect on the abundance of the apramycin resistance gene aac(3)-IV . Methods A cluster-randomised non-inferiority field trial was conducted in 518 diarrhoeic piglets across 28 pens in a commercial herd. Piglets received apramycin for 3 or 7 days. Clinical cure was assessed by faecal scoring at end of treatment (EOT) and at a common Day 8 timepoint after treatment initiation. A non-inferiority margin of − 10% points was applied. Pen-level aac(3)-IV/ 16S abundance was quantified by qPCR. Results Non-inferiority of the 3-day course was not demonstrated at EOT (184/257 [71.6%] vs. 204/261 [78.2%]; risk difference − 0.063, 95% CI − 0.184 to 0.058), but was demonstrated at the common Day 8 timepoint (215/257 [83.7%] vs. 204/261 [78.2%]; risk difference + 0.055, 95% CI − 0.076 to 0.184). At EOT, both groups showed significant reductions in pen-level log10( aac(3)-IV /16S) from baseline, with a greater median decline in the 3-day group than in the 7-day group (− 2.99 vs. − 1.71; p = 0.0258). At Day 8, baseline-adjusted change in relative aac(3)-IV abundance did not differ significantly between groups (− 1.24 vs. − 1.70; p = 0.696). Relative gene abundance was not associated with clinical cure. Conclusions A 3-day apramycin course did not meet the predefined non-inferiority criterion at end of treatment, where the two groups were assessed at different stages of recovery. However, when evaluated at the common Day 8 timepoint, the 3-day course achieved clinical outcomes comparable to the 7-day course, with no evidence of increased resistance gene abundance. These findings support the possibility of shortened treatment duration as a pragmatic antimicrobial stewardship strategy in porcine PWD and as a potential means to reduce antimicrobial consumption in livestock production.